An emergency department intervention to protect an overlooked group of children at risk of significant harm. Issue 6 (22nd May 2009) - Kaye, P; Taylor, C; Barley, K; Powell-Chandler, A
Abstract : Background: Parental psychiatric disorder, especially depression, personality disorder and deliberate self-harm, is known to put children at greater risk of mental illness, neglect or physical, emotional and sexual abuse. Without a reliable procedure to identify children of parents presenting with these mental health problems, children at high risk of significant harm can be easily overlooked. Although deliberate self-harm constitutes a significant proportion of emergency presentations, there are no guidelines which address the emergency physician's role in identifying and assessing risk to children of these patients. Methods: A robust system was jointly developed with the local social services child protection team to identify and risk-stratify children of parents with mental illness. This allows us to intervene when we identify children at immediate risk of harm and to ensure that social services are aware of potential risk to all children in this group. The referral process was audited repeatedly to refine the agreed protocol. Results: The proportion of patients asked by the emergency department personnel about dependent children increased and the quality of information received by the social services child protection team improved. Conclusions: All emergency departments should acknowledge the inadequacy of information available to them regarding patients' children and consider a policy of referral to social services for all children of parents with mental health presentations. This process can only be developed through close liaison within the multidisciplinary child protection team.